A perception‐based emotion contagion model in crowd emergent evacuation simulation. (8th May 2018) - Liu, Zhen; Liu, Tingting; Ma, Minhua; Hsu, Hui‐Huang; Ni, Zhongrui; Chai, Yanjie
Abstract: With the increasing number of emergencies, the crowd simulation technology has attracted wide attention in the recent years. Existing emergencies have shown that individuals are easy to be influenced by others' emotion during the evacuation. This will make it easier for people to aggregate together and increase security risks. Some of the existing evacuation models without considering emotion are therefore not suitable for describing crowd behaviors in emergencies. We propose a perception‐based emotion contagion model and use multiagent technology to simulate crowd behaviors. Navigation points are introduced to guide the movement of the agents. Based on the proposed model, a prototype simulation system for crowd emotion contagion is developed. The comparative simulation experiments verify that the model can effectively deduct the evacuation time and crowd emotion contagion. The proposed model could be an assistant analysis method for crowd management in emergencies. Abstract : A perception‐based emotion contagion model is proposed to simulate the evacuation. The red area on the left represents the spreading fire and the yellow area represents the transmission area of the fire information, emotion contagion of agents is visualized with red color.